Applications of optical-cavity-based spectroscopic techniques in the condensed phase - Li, J (2014)
Cavity ring-down spectroscopy (CRDS) and cavity enhanced absorption spectroscopy (CEAS) are two well-established absorption spectroscopic techniques originally developed for gas-phase samples. Condensed-phase applications of these techniques still remain rare, complicated as they are by additional background losses induced by condensed-phase samples as well as the intracavity components in which the sample is constrained. This thesis is concerned with the development and application of optical-cavity-based techniques in the condensed phase. Polarization-dependent evanescent wave CRDS (EW-CRDS) has been used to study the molecular orientation at the solid/air and solid/liquid interfaces. An increase in average orientation angle with respect to the surface normal has been observed for both methylene blue and coumarin molecules as a function of coverage at the fused silica/air interface. An orientation-angle-dependent photobleaching of pyridin molecules at the fused silica/methanol interface have also been observed. EW-CRDS has also been used to monitor slow in situ photobleaching of thin dye films deposited on the prism surface. The photobleaching dynamics is interpreted as a combination of first- and second-order processes. A significant fraction of this thesis has been devoted to studying magnetic field effects (MFEs) on the kinetics of the radical pair (RP) reactions in solution, in an effort to understand the ability of animals to sense the geomagnetic field. Two novel optical-cavity-based techniques – broadband CEAS (BBCEAS) and CRDS have been developed for this purpose. BBCEAS uses a supercontinuum (SC) source as the cavity light source and a CCD camera as photodetector, enabling simultaneous acquisition of absorption spectrum across the whole visible region (400 – 800 nm). In CRDS, a tunable optical parametric oscillator has been used as the cavity light source. Combined with the switching of external magnetic field (SEMF) method, this technique allows the decay kinetics of the geminate RPs to be monitored, with nanosecond resolution. Both BBCEAS and CRDS provide sensitivity superior to single-pass transient absorption (TA), a technique traditionally used in the MFE studies. A series of photochemical systems have been studied by BBCEAS and CRDS, respectively, among which, the MFEs of drosophila melanogaster cryptochrome has been observed. Importantly, this is the first time an MFE has been observed in an animal cryptochrome, and provides key supporting evidence for the cryptochrome hypothesis of magnetoreception in animals. Besides the optical-cavity-based techniques, a novel fluorescence detection method of MFEs has also been demonstrated. This technique proved ultrahigh sensitivity when applicable.